Enhancement of cherry tomato (Solanum lycopersicum var. cerasiforme) growth, physiology, yield and quality in relation to media types, shading and elevated carbon dioxide under different greenhouse systems - Mohmad Hairin, Nur Eastiharah (2019)
Cherry tomato (Solanum lycopersicum var. cerasiforme) is crisp and juicy compared to regular tomato. The bite-sized cherry tomato leads to high demand in regular consumption among community for healthy snacking. However, uncertainty weather pattern was determined as one of the factors that can impact to the food production. Due to the climate changes impact around the world, tomato was found to have better growth, yield and good quality if it is been grown under greenhouse conditions. However, the environmental conditions inside the greenhouse such as media types, amount of light intensity and level of carbon dioxide (CO2) need to be optimised to improve the growth performance, yield production and quality of tomato. Thus, the objectives of this study were to investigate the effect media type, light intensity level and CO2 elevation on growth performance, physiology changes, yield production and quality of tomato grown under greenhouse conditions. In Experiment 1, seedlings variety Ruby Red cherry tomato was planted using three different types of media [coconut coir dust (CCD), mixed soil, and top soil] under two different greenhouse systems; smart greenhouse system (SGS) and conventional greenhouse system (CGS). The plants were observed at 30, 60 and 90 days after transplant (DAT). The experiment was arranged in randomized complete block design (RCBD). Plant height, total leaf area, shoot and root dry, root to shoot ratio (R:S), photosynthetic rate, stomatal conductance, transpiration rate, and water use efficiency and yield showed the best performance and significantly highest when the plant grown under CCD. In Experiment 2, Ruby Red cherry tomato seedlings was grown using CCD media which was optimized from Experiment 1. The seedling was then shaded using 0, 50% and 70% black netting to allow 100%, 50% and 30% light penetration, respectively. The plant was placed under greenhouses elevated with 800 ppm CO2 elevation at 8-10 am daily(SGS) and non-elevated CO2 (CGS) as control. Exposing tomato seedling in higher CO2 concentration reduced plant height, total leaf area and total biomass than control. The number of lateral roots increased under SGS compared to CGS and that the length of the roots increased as well. Upon CO2 enrichment happened, there was a reduction in stomatal conductance and transpiration rate which reduced the loss of water in the atmosphere. Higher concentration CO2 level can contribute heat stress to the plant due to the increase in temperature up to 52°C. As consequently fruit setting was delayed about 3 weeks as compared to the plant grown under CGS. Nevertheless, tomato plant received 50% of light penetration has the highest lycopene content in both greenhouses compared to other shading level. In conclusion, CCD is recommended as growing media and shading did not help in reducing temperature under elevated CO2 greenhouse especially in tropical region.